Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1096/fj.09-130005
|View full text |Cite
|
Sign up to set email alerts
|

Indolyl‐quinuclidinols inhibit ENOX activity and endothelial cell morphogenesis while enhancing radiation‐mediated control of tumor vasculature

Abstract: There is a need for novel strategies that target tumor vasculature, specifically those that synergize with cytotoxic therapy, in order to overcome resistance that can develop with current therapeutics. A chemistry-driven drug discovery screen was employed to identify novel compounds that inhibit endothelial cell tubule formation. Cell-based phenotypic screening revealed that noncytotoxic concentrations of (Z)-(+/-)-2-(1-benzenesulfonylindol-3-ylmethylene)-1-azabicyclo[2. 2.2]octan-3-ol (analog I) and (Z)-(+/-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 39 publications
(53 reference statements)
3
44
0
Order By: Relevance
“…In some experiments, NADH oxidation was monitored after heating to 50 C for 10 min and removing heat-denatured proteins by centrifugation at 6000 rpm for 5 min (Yantiri and Morré 2001). NAD(P)H oxidase activity was also measured by monitoring the reduction of WST-1, a cellimpermeable artificial electron acceptor (Geng et al 2009). Briefly, intact platelets (1 Â 10 8 ) were incubated with 0.5 mM WST-1 and 0.2 mM NADH or 0.2 mM NADPH.…”
Section: Nad(p)h Oxidase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In some experiments, NADH oxidation was monitored after heating to 50 C for 10 min and removing heat-denatured proteins by centrifugation at 6000 rpm for 5 min (Yantiri and Morré 2001). NAD(P)H oxidase activity was also measured by monitoring the reduction of WST-1, a cellimpermeable artificial electron acceptor (Geng et al 2009). Briefly, intact platelets (1 Â 10 8 ) were incubated with 0.5 mM WST-1 and 0.2 mM NADH or 0.2 mM NADPH.…”
Section: Nad(p)h Oxidase Activitymentioning
confidence: 99%
“…Platelets also showed an electron donor preference, since the rate of NADHdependent WST-1 reduction was significantly higher than that of NADPH-dependent WST1 reduction (Figure 2A). It has been reported that the Ecto-NOX proteins may be responsible for cell surface reduction of WST-1 (Geng et al 2009); none the less, this tetrazolium salt has also been used for detection of superoxide or superoxide-generating enzymes (Oritani et al 2004, Tan andBerridge 2010). In order to circumvent the misunderstanding that could come from the use of WST-1, we also monitored the disappearance of NAD(P)H at 340 nm.…”
Section: Ecto-nox1 Is Present In Human Plateletsmentioning
confidence: 99%
“…Inhibition of ENOX1 has been reported to decrease angiogenesis in tumour growth. 17 ENOX1 was found with a high but not exclusive expression level in fetal brain (see http://biogps.org), but no other data are available in the literature to incriminate this gene in the context of psychomotor delay. Comparative analysis of deleted intervals in delayed and non-delayed patients identified PCDH8 as a candidate gene for psychomotor delay (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In combination with other results, however, endothelial cell assays can be a source of lead compounds. For instance, Sekhar et al combined observations from a chemistry-driven drug discovery screen for inhibitors of endothelial cell tubule formation with biochemical pathway screening and shRNA suppression to identify compounds to pursue as drug leads, and also validate ENOX1 as a target for enhancing radiation response of tumors [49]. Other endothelial cell strategies have looked to capitalize on differences between tumor and normal endothelial cells.…”
Section: In Vitro Modelsmentioning
confidence: 99%